2017
DOI: 10.1080/15563650.2017.1401080
|View full text |Cite
|
Sign up to set email alerts
|

Is naloxone the best antidote to reverse tramadol-induced neuro-respiratory toxicity in overdose? An experimental investigation in the rat

Abstract: Diazepam/naloxone combination is the most efficient antidote to reverse tramadol-induced CNS toxicity in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…It was clear that co-ingestion of other drugs or agents significantly affect the PSS of the studied patients. This result was extremely logic as the co-ingested drugs were mostly tramadol accounting for 44.59% of coingested substances followed by antipsychotics, mainly clozapine (14.86%), which are well-known to be unsafe medications and greatly affect the clinical course of poisoning owing to tramadol-induced respiratory depression and antipsychotics-induced cardiotoxicity (Lagard et al, 2018;Li et al, 2019). In studies done by Bonar et al (2014) and Law et al (2015), alcohol topped the list of co-ingested agents (96%), followed by cannabis and prescriptive opioids in USA.…”
Section: Discussionmentioning
confidence: 99%
“…It was clear that co-ingestion of other drugs or agents significantly affect the PSS of the studied patients. This result was extremely logic as the co-ingested drugs were mostly tramadol accounting for 44.59% of coingested substances followed by antipsychotics, mainly clozapine (14.86%), which are well-known to be unsafe medications and greatly affect the clinical course of poisoning owing to tramadol-induced respiratory depression and antipsychotics-induced cardiotoxicity (Lagard et al, 2018;Li et al, 2019). In studies done by Bonar et al (2014) and Law et al (2015), alcohol topped the list of co-ingested agents (96%), followed by cannabis and prescriptive opioids in USA.…”
Section: Discussionmentioning
confidence: 99%
“…[15]. On the other hand, while the evidence could not support the preventive effect of naloxone in such patients [54], seizures may be precipitated by injecting naloxone, accompanying high doses of tramadol [2,7,31,60,75]. Interestingly, recent meta-analyses have shown that the occurrences of seizures was not related to naloxone administration [67].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Intubation/ventilation and administration of naloxone are implemented to treat respiratory depression or tramadolinduced apnea [16,70,131,132]. Some studies suggested that naloxone administration might cause seizure in tramadol intoxication and recommended against routine administration of naloxone for treating tramadol poisoning [10, 60,133]. However, a recent meta-analysis showed that naloxone administration does not increase the risk of seizure in tramadol poisoned patients [67].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increasing numbers of tramadol overdose and fatalities in recent decades, this drug has been classi ed as controlled substance in several countries [2]. Tramadol overdose can lead to loss of consciousness, seizures, respiratory depression, serotonin syndrome, and death [3,4]. However, the molecular and biochemical mechanisms of tramadol toxicity are still poorly understood [5].…”
Section: Introductionmentioning
confidence: 99%